Inducible Lentivirus-Mediated siRNA against TLR4 Reduces Nociception in a Rat Model of Bone Cancer Pain - Ruirui Pan; Huiting Di; Jinming Zhang; Zhangxiang Huang; Yuming Sun; Weifeng Yu; Feixiang Wu (Mediators of Inflammation)
Although bone cancer pain is still not fully understood by scientists and clinicians alike, studies suggest that toll like receptor 4 (TLR4) plays an important role in the initiation and/or maintenance of pathological pain state in bone cancer pain. A promising treatment for bone cancer pain is the downregulation of TLR4 by RNA interference; however, naked siRNA (small interference RNA) is not effective in long-term treatments. In order to concoct a viable prolonged treatment for bone cancer pain, an inducible lentivirus LvOn-siTLR4 (tetracycline inducible lentivirus carrying siRNA targeting TLR4) was prepared and the antinociception effects were observed in bone cancer pain rats induced by Walker 256 cells injection in left leg. Results showed that LvOn-siTLR4 intrathecal injection with doxycycline (Dox) oral administration effectively reduced the nociception induced by Walker 256 cells while inhibiting the mRNA and protein expression of TLR4. Proinflammatory cytokines as TNF-α and IL-1β in spinal cord were also decreased. These findings suggest that TLR4 could be a target for bone cancer pain treatment and tetracycline inducible lentivirus LvOn-siTLR4 represents a new potential option for long-term treatment of bone cancer pain.